Optimization of Process Variables Affecting the Production of Extracellular Protease by Kluyveromyces marxianus - Stergiou, Panagiota-Yiolanda; Foukis, Athanasios; G. Theodorou, Leonidas; Papagianni, Maria; M. Papamichael, Emmanuel (Current Biotechnology, 2013)
The optimized production of extracellular protease by Kluyveromyces marxianus IF0 0288 is investigated in yeast medium containing glucose as the carbon source in fully aerobic batch fermentation (150 rpm). Four parameters - type of nitrogen source, initial culture pH, temperature and length of fermentation- influencing the growth and protease production, were considered using both the “one variable at a time” approach and response surface methodology (RSM). Experimental and statistical evidence is presented for 36-fold increase in protease volumetric activity during 72 hours of fermentation with conventionally optimized nutrition (0.04% w/v bovine serum albumin) and cultivation (pH 5.5, 25oC) conditions. The optimal initial pH-value 5.46 and temperature 25.9oC were identified by the RMS and further improved on application both the volumetric activity (42.5-fold) and specific protease activity (51-fold). The results provide for the first time the evidence that K. marxianus is potentially an efficient producer of extracellular protease.
Keywords: serine protease